2012
DOI: 10.1103/physreve.85.031303
|View full text |Cite
|
Sign up to set email alerts
|

Force chains and contact network topology in sheared packings of elongated particles

Abstract: By means of contact dynamic simulations, we investigate the contact network topology and force chains in two-dimensional packings of elongated particles modeled by rounded-cap rectangles. The morphology of large packings of elongated particles in quasistatic equilibrium is complex due to the combined effects of local nematic ordering of the particles and orientations of contacts between particles. We show that particle elongation affects force distributions and force/fabric anisotropy via various local structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
100
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(114 citation statements)
references
References 42 publications
13
100
1
Order By: Relevance
“…The increase of these interactions has also been observed in experiments [42] as well as in numerical simulations with elongated particles in 2D [15,18].…”
Section: Summary and Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…The increase of these interactions has also been observed in experiments [42] as well as in numerical simulations with elongated particles in 2D [15,18].…”
Section: Summary and Discussionsupporting
confidence: 50%
“…Due to dynamics in continuous shearing, this ordering phenomenon emerges even in systems composed of particles with very low platyness with a shape differing only slightly from spherical shape. This kind of ordering has previously been observed in experiments [27,22] and numerical simulations mainly with two-dimensional elongated particles [28,15,18]. Regarding the privileged direction of alignment, we found that, as platyness increases, this direction gradually changes from that of the major principal stress to a direction that is perpendicular to the shear direction.…”
Section: Summary and Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In CD, an iterative algorithm based on nonlinear Gauss-Seidel iterations is used to determine the contact forces and particle velocities simultaneously at all potential contacts. The CD method has been extensively employed for the simulation of granular materials in 2D and 3D [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72].…”
Section: Bonded Cell Modelmentioning
confidence: 99%